Expandable vs Static Cages in Transforaminal Lumbar Interbody Fusion: Radiographic Comparison of Segmental and Lumbar Sagittal Angles. Issue 1 (23rd March 2017) - Yee, Timothy J.; Joseph, Jacob R.; Terman, Samuel W.; Park, Paul
Abstract: BACKGROUND: One criticism of transforaminal lumbar interbody fusion (TLIF) is the inability to increase segmental lordosis (SL). Expandable interbody cages are a relatively new innovation theorized to allow improvement in SL. OBJECTIVE: To compare changes in SL and lumbar lordosis (LL) after TLIF with nonexpandable vs expandable cages. METHODS: We performed a retrospective cohort study of patients who were ≥18 years old and underwent single-level TLIF between 2011 and 2014. Patients were categorized by cage type (static vs expandable). Primary outcome of interest was change in SL and LL from preoperative values to those at 1 month and 1 year postoperatively. RESULTS: A total of 89 patients were studied (48 nonexpandable group, 41 expandable group). Groups had similar baseline characteristics. For SL, median (interquartile range) improvement was 3° for nonexpandable and 2° for expandable (unadjusted, P = .09; adjusted, P = .68) at 1 month postoperatively, and 3° for nonexpandable and 1° for expandable (unadjusted, P = .41; adjusted, P = .28) at 1 year postoperatively. For LL, median improvement was 1° for nonexpandable and 2° for expandable (unadjusted, P = .20; adjusted, P = .21), and 2° for nonexpandable and 5° for expandable (unadjusted, P = .15; adjusted, P = .51) at 1 year postoperatively. After excluding parallel expandable cages, there was still no difference in SL or LL improvement at 1 month or 1 year postoperatively between static and expandable cages (both unadjusted and adjusted, P > .05). CONCLUSION: Patients undergoing single-level TLIF experienced similar improvements in SL and LL regardless of whether nonexpandable or expandable cages were placed.